PENGAWET MAKANAN: Sebuah Bahasan Untuk Penetapan Halalan Toyyiban - Hayati, Elok Kamilah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
As the primary needs of human being, food we consume must be halal and good as prescribed by Muslim law which is explicitly stated in Quran and Hadith. Deciding the food is halal or not can be detected from its benefit and disadvantage, and also from its processing. The development of food industry has brought better change both qualitatively and quantitatively on the food. This caused a significant improvement on food ingredients such as preservative and texture of the food. The consumer needs fresh, cheap, and easy-serving as the consequence of practical life. The high demand on economic interest and the complexity of food causes the increase of chemical substance as the preservative, such as formalin. The use of preservative that is to preserve foodstuffs against decay is very dangerous as it brings negative effect to our health. Therefore, the idea of back to nature which promotes the optimal use of natural food must be highly recommended. This can, physiologically, be received easily into our body.